Plan estratégico de ventas para los productos y servicios de la Distribuidora Telefonía móvil DIGITAL PHONE, ubicada en el cantón Quevedo, año 2014. - Cruz Tachón, José Delfín (2015)
Currently no formalized increased competition and the presence of powerful companies that have high prestige that invest a high budget promotional advertising products and services, cause decline in profit margins in recent years in Digital Phone. First a market study was conducted to determine the behavior of the target audience, who are current customers of the company and the general public. The inductive method was used to draw general conclusions, the same that was used to make the discussion of the thesis. The statistical method allowed the development stages of the process in the management of strategic planning applied in research to determine the comparative relationship between sales of the previous two years and the current period. The analytical method was used to determine the different parts of the problem and analysis of the data after tabulation of surveys to customers and the general public was also performed. A sample of 381 respondents was applied and was distributed in 300 surveys to the general public and 81 surveys for existing customers, their choice was random and distributed using the sampling technique. The level of confidence in Digital Phone, indicates that 64% said excellent, plus there is a significant margin for different opinions, that is, there are customers who do not share that view. This provides the opportunity to analyze what aspects should be improved in order to find alternatives to optimize the percentage differential, and thus achieve greater confidence and interest of customers. The interview took place the owner manager of Digital Phone, where information necessary for the conclusions of the analysis and implementation of strategic sales plan was obtained. It is concluded that the strategic sales plan is feasible and profitable for the company, the indicators show that the budgeted profit increased by 103% over the previous year.